E-SAMSAT IN REALIZING PUBLIC SERVICES AT THE SAMSAT OFFICE IN GOWA DISTRICT - Rianti, Rianti; Nur, Andi Cudai; Guntur, Muhammad; Rukmana, Novayanti Sopia (Universitas Negeri Makassar, 2025)
This study aims to determine the quality of e-Samsat in realizing public services at the Samsat Office in Gowa Regency and to determine the quality of public services from the e-Samsat public service system in the Samsat Office in Gowa Regency. This research uses a qualitative approach with descriptive methods. Data collection was carried out by field observations, interviews and documentation. Data analysis techniques use data condensation, data presentation and conclusion. The results of this study indicate that the success of e-Samsat in realizing public services at the Samsat Office in Gowa Regency has not been optimally successful. This can be seen through three research indicators. The successful indicator is Accountability with a clear type of service when using the e-Samsat service. Responsiveness and Responsibility indicators that have not been successful in implementing this e -Samsat service system. The e-Samsat service system at the Gowa Regency Samsat office has not been able to create quality services.